Oxidative stress and altered levels of antioxidants in adolescents with Down syndrome during pre-exercise and post-exercise - Ozbey, Ulku; Arslan, Cengiz; Savucu, Yuksel; Erisir, Mine; Seyran, Ayse (Academic Journals, 2012)
The aim of this study was to determine the influence of exercise on activity of erythrocyte superoxide dismutase (SOD), glutathione peroxidase (GPx), catalase (CAT) and plasma malondialdehyde (MDA), beta-carotene, retinol levels in adolescents with Down syndrome (DS). Twenty adolescents with DS (14.86 +/- 7.07 years) performed a 12-week training program. Body composition was measured by bioelectric impedance method. SOD, GPx, CAT, MDA, retinol, beta-carotene levels was determined spectrophotometrically. When compared to baseline, MDA level was increased (P<0.05). SOD, GPx activities and beta-carotene level were decreased (P<0.05). There was no difference during pre-post exercise in terms of CAT activity and retinol level (P>0.05). The mean value of percentage of fat mass was reduced. Regular exercise decreased SOD, GPx activities and beta-carotene level and did not affect CAT activity and retinol level in individuals with DS. Exercise increases oxidative stress depending on level of training.
Keywords: Down syndrome; exercise; body composition; antioxidant enzyme; obesity; fat mass percentage